Perbedaan Citra Tubuh Primigravida Dengan Multigravida - Yusni - Seftiani; Widia - Lestari; Darwin - Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Purpose of this study is to determine differences in body image primigravida with multigravida. Research method is descriptive with study comporative. Research conducted at the beginning of the hospital Awal Bross Pekanbaru to sixty respondents. Sampling method is accidental sampling technique. Measuring instrument used was a questionnaire that had been tested for validity and reliability. Analysis used is univariate and bivariate analysis by using chi-square test. The results showed a significant difference between body image primigrafida with multigrafida (p value=0.004). The results of this study recommend health workers provide counseling of body image changeover during pregnancy. Keyword: body image, primigravida, multigravida.